Edukasi terhadap Self Efficacy dan Kualitas Hidup Pasien Kanker Kolorektal yang Menjalani Kemoterapi - Sagala, Martha Sutriska; Zahara, Siti; Hasnida, Hasnida (Journal of Telenursing (JOTING), 2023)
This study aims to identify the effect of education on self-efficacy and quality of life in colorectal cancer patients undergoing chemotherapy. The method used is quantitative, using a quasi-experimental design with a nonequivalent control group pre-posttest-only design method with a sample size of 56 people, using the GSE (General Self Efficacy) questionnaire instrument and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC QLQ). -C30). The results of the research show that education affects the self-efficacy of colorectal cancer patients undergoing chemotherapy with a p-value <0.05, and education affects the quality of life of colorectal cancer patients undergoing chemotherapy with a p-value <0.05. The conclusion is that educational interventions positively increase self-efficacy and quality of life in colorectal cancer patients undergoing chemotherapy. Keywords: Education, Colorectal Cancer, Quality of Life, Self Efficacy